A glycoproteomic approach reveals that the S-layer glycoprotein of Lactobacillus kefiri CIDCA 83111 is O- and N-glycosylated - Cavallero, Gustavo Javier (2017)
In Gram-positive bacteria, such as lactic acid bacteria, general glycosylation systems have not been documented so far. The aim of this work was to characterize in detail the glycosylation of the S-layer protein of Lactobacillus kefiri CIDCA 83111. A reductive β-elimination treatment followed by anion exchange high performance liquid chromatography analysis was useful to characterize the O-glycosidic structures. MALDI-TOF mass spectrometry analysis confirmed the presence of oligosaccharides bearing from 5 to 8 glucose units carrying galacturonic acid. Further nanoHPLC-ESI analysis of the glycopeptides showed two O-glycosylated peptides: the peptide sequence SSASSASSA already identified as a signature glycosylation motif in L. buchneri, substituted on average with eight glucose residues and decorated with galacturonic acid and another O-glycosylated site on peptide 471–476, with a Glc5–8GalA2 structure. As ten characteristic sequons (Asn-X-Ser/Thr) are present in the S-layer amino acid sequence, we performed a PNGase F digestion to release N-linked oligosaccharides. Anion exchange chromatography analysis showed mainly short N-linked chains. NanoHPLC-ESI in the positive and negative ion modes were useful to determine two different peptides substituted with short N-glycan structures. To our knowledge, this is the first description of the structure of N-glycans in S-layer glycoproteins from Lactobacillus species. Significance A detailed characterization of protein glycosylation is essential to establish the basis for understanding and investigating its biological role. It is known that S-layer proteins from kefir-isolated L. kefiri strains are involved in the interaction of bacterial cells with yeasts present in kefir grains and are also capable to antagonize the adverse effects of different enteric pathogens. Therefore, characterization of type and site of glycosidic chains in this protein may help to understand these important properties. Furthermore, this is the first description of N-glycosidic chains in S-layer glycoprotein from Lactobacillus spp.